The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 16: Depart Switzerland - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 16: Depart$1! =(B" is part of an autobiography written between 1789-1798. Giacomo Casanova chronicles his adventurous life as an 18th-century Venetian libertine in this sprawling 3,700-page memoir. Written in French, the manuscript covers his experiences through 1774, though censored versions circulated for over a century before the original text was finally published. This volume captures another chapter in the legendary seducer's eventful journey through European high society, scandal, and intrigue. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2004-12-11
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography